The Las Gościbia – land of cascades and waterfalls - Waśkowska, Anna; Stadnik, Renata; Miśkiewicz, Krzysztof (Geotourism/Geoturystyka)
The “Las Gościbia” includes the northern slopes of Babica Mt. (Beskid Makowski) in the catchment area of a mountain stream called Gościbia. It is located within the Magura Nappe in the Siary Zone (Outer Carpathians). In the deeply cut valleys there is exposed continuously profile of the flysch deposits of Eocene-Oligocene age (Pasierbiec Sandstone, Zembrzyce Shale, Wątkowa Sandstone). The special value of the “Las Gościbia” are cascades and waterfalls, which are numerous here in stream valleys. Their abundance, the heterogeneous nature and high aesthetic values determined a high educational and geotourist potential.